Research on shear-slip characteristics with different-size rectangular zigzag gouge by double-direct tests - Yang Liu; Cai-Ping Lu; Tong-bin Zhao (International Journal of Distributed Sensor Networks)
We designed and manufactured several types of simulated faults with different-size rectangular zigzag gouges, and sheared them by traditional double-direct shear tests. Simultaneously, the shear force and corresponding acoustic emissions were recorded during shear-slip of rectangular zigzag gouge, and the variations of shear force and acoustic emission energy characteristics related to shear-slip events were analyzed. Especially, the relationship between shear-slip characteristics and zigzag length and width was also revealed. In addition, the significant differences of slip characteristic parameters between shear-slip of an intact zigzag and friction and sliding on rough plane of a sheared zigzag were summarized, and it might be used to judge the different stages of a fault slip with zigzag gouge. In conclusion, this work may reveal the characteristics of shear-slip and friction under conditions of different-size rectangular zigzag gouges of simulated fault and thus provide valuable insights into precursors of earthquake.